Credit Rating Agencies: The Main Lacuna in EU Regulation Governing Conflicts of Interest - Alessandra Chirico (CEPS, Centre for European Policy Studies, 2008)
Credit Rating Agencies play a key role in European capital markets today, publishing ratings on the creditworthiness of issuers/issues of debt securities. Independent, objective and internationally consistent credit ratings raise the integrity, transparency and competitiveness of capital markets, lower the costs of capital for issuers and contribute to investor protection. Moreover, ratings are widely used by investors as a guide to the creditworthiness of the issuers of debt, and in financial covenants. As a result, credit rating agencies play a major role not only in the pricing of debt securities, but also in the regulatory process. It may well happen, in fact, that regulators co-opt rating agencies as information-producing agents for regulatory purposes. In this way, when ratings serve not just as a tool for investors but become the very foundation for regulation, they become extremely powerful, and as a consequence, the risk that conflicts of interest will arise becomes much sharper.
Keywords: 330; Credit rating agencies; financial market supervision; conflicts of interest; MiFID; financial markets regulation; transparency; European Commission; Financial market; Regulation; Regulatory agency; Credit rating